2022
DOI: 10.1002/jcsm.13149
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy of ultrasound for sarcopenia diagnosis: A systematic review and meta‐analysis

Abstract: Muscle ultrasound is an emerging tool for diagnosing sarcopenia. This review aims to summarize the current knowledge on the diagnostic test accuracy of ultrasound for the diagnosis of sarcopenia. We collected data from Ovid Medline, Embase and the Cochrane Central Register of Controlled Trials. Diagnostic test accuracy studies using muscle ultrasound to detect sarcopenia were included. Bivariate random‐effects models based on sensitivity and specificity pairs were used to calculate the pooled estimates of sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 48 publications
(211 reference statements)
1
27
0
Order By: Relevance
“…While ultrasonographic evaluation of lower limb muscles, such as rectus femoris 50 and gastrocnemius 51 MT, has been commonly studied in the literature, and even with recommended cut‐off values, the upper limb muscles have received less attention 42 . It is because the lower limb muscles are simpler to measure and highly related to mobility and activities of daily living than the trunk or head muscles 52 . Additionally, another cause may be the age‐related volumetric changes in the upper limb muscles 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While ultrasonographic evaluation of lower limb muscles, such as rectus femoris 50 and gastrocnemius 51 MT, has been commonly studied in the literature, and even with recommended cut‐off values, the upper limb muscles have received less attention 42 . It is because the lower limb muscles are simpler to measure and highly related to mobility and activities of daily living than the trunk or head muscles 52 . Additionally, another cause may be the age‐related volumetric changes in the upper limb muscles 53 .…”
Section: Discussionmentioning
confidence: 99%
“…42 It is because the lower limb muscles are simpler to measure and highly related to mobility and activities of daily living than the trunk or head muscles. 52 Additionally, another cause may be the age-related volumetric changes in the upper limb muscles. 53 However, upper limb exercises have been shown to improve survival rates and physical disabilities due to muscle atrophy.…”
Section: Hazard Ratio 95% Confidence Interval Pmentioning
confidence: 99%
“…There are concerns about reproducibility in individuals with higher body fat levels, as ultrasonography may encounter difficulties in accurately measuring muscle thickness due to interference from adipose tissue. 28 As a result, utilizing imaging studies commonly employed to assess other medical conditions could enhance the screening for sarcopenia and increase the treatment of this usually overlooked condition. 10 Regional CT and MRI could become accurate and more practical non-invasive methods to quantify muscle volume.…”
Section: Discussionmentioning
confidence: 99%
“…However, it requires trained professionals, specialized equipment and extra time. There are concerns about reproducibility in individuals with higher body fat levels, as ultrasonography may encounter difficulties in accurately measuring muscle thickness due to interference from adipose tissue 28 …”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that, in the thigh, muscle groups might have different performances to detect sarcopenia, with the highest performance observed with the rectus femoris as compared to vastus intermedius or quadriceps femoris. 7 Interestingly, other muscle groups of the lower limb (e.g., gastrocnemius) but also belonging to other parts of the body (e.g., rectus abdominis) have shown similar performance as the rectus femoris. Hence, further studies performing proper multisite evaluations of US-based sarcopenia are needed to search for the best muscle groups (head-neck vs. trunk vs. limbs) and their parameters (thickness vs. area) that reflect whole-body muscle mass in advanced liver disease.…”
mentioning
confidence: 99%